Acylated 2-(N-arylaminomethylene)benzo[b]thiophene-3(2H )-Ones: Molecular Switches with Varying Migrants and Substituents. (16th June 2009) - Dubonosov, Alexander D.; Rybalkin, Vladimir P.; Popova, Lydia L.; Tsukanov, Alexey V.; Revinsky, Yurii V.; Bren, Vladimir A.; Minkin, Vladimir I.
Abstract : Synthesis and properties of photochromic acylated 2-(N -arylaminomethylene)benzo[b ]thiophene-3(2H )-ones are described. Their structure largely depends on the nature of acyl migrant and in a less degree on N-aryl substituent.